La lúdica como estrategia didáctica para la mitigación de conductas disruptivas y el fortalecimiento de la convivencia escolar (2020)
This research seeks to implement playfulness as a didactic strategy for the mitigation of disruptive behaviors. Starting from the observation and analysis of behavioral phenomena of children in basic education; applying methods, techniques, instruments, data collection and establishing a correlation between the dependent and independent variables, with the Pearson correlation coefficient. A graph of high negative slope was obtained, justifying contributions from this research: the application of playful methodological strategies to mitigate disruptive behaviors, finding that, when applying the didactic activities, the children improved their personal relationships, strengthening school coexistence.